Strong In Vivo Inhibition of HIV-1 Replication by Nullbasic, a Tat Mutant - Hongping Jin; Yifan Sun; Dongsheng Li; Min-Hsuan Lin; Mary Lor; Lina Rustanti; David Harrich (mBio, 2019)
ABSTRACT Nullbasic is a mutant form of the HIV-1 transcriptional activator protein (Tat) that strongly inhibits HIV-1 transcription and replication in lymphocytes in vitro. To investigate Nullbasic inhibition in vivo, we employed an NSG mouse model where animals were engrafted with primary human CD4+ cells expressing a Nullbasic-ZsGreen1 (NB-ZSG) fusion protein or ZSG. NB-ZSG and ZSG were delivered by using a retroviral vector where CD4+ cells were transduced either prior to (preinfection) or following (postinfection) HIV-1 infection. The transduced cells were analyzed in vitro up to 10 days postinfection (dpi) and in vivo up to 39 dpi. Compared to ZSG, NB-ZSG strongly inhibited HIV-1 replication both in vitro and in vivo using preinfection treatment. In vitro, HIV-1 mRNA levels in cells were reduced by up to 60-fold. In vivo, HIV-1 RNA was undetectable in plasma samples during the course of the experiment, and HIV-1 mRNA levels in resident CD4+ cells in organ tissue were reduced up to 2,800-fold. Postinfection treatment of HIV-1-infected cells with NB-ZSG attenuated HIV-1 infection for up to 14 days. In vitro, a 25-fold reduction of viral mRNA in cells was observed but diminished to a <2-fold reduction by 10 dpi. In vivo, HIV-1 RNA was undetectable in plasma of NB-ZSG mice at 14 dpi but afterwards was not significantly different between NB-ZSG mice and control mice. However, we observed higher levels of CD4+ cells in NB-ZSG mice than in control mice, suggesting that NB-ZSG imparted a survival advantage to HIV-1-infected animals. IMPORTANCE HIV-1 infection is effectively controlled by antiviral therapy that inhibits virus replication and reduces viral loads below detectable levels in patients. However, therapy interruption leads to viral rebound due to latently infected cells, which serve as a source of continued viral infection. Interest in strategies leading to a functional cure for HIV-1 infection by long-term or permanent viral suppression is growing. Here, we show that a mutant form of the HIV-1 Tat protein, referred to as Nullbasic, inhibits HIV-1 transcription in infected CD4+ cells in vivo. Analysis shows that stable expression of Nullbasic in CD4+ cells could lead to durable anti-HIV-1 activity. Nullbasic, as a gene therapy candidate, could be a part of a functional-cure strategy to suppress HIV-1 transcription and replication.